Negative pole piece as well as preparation method and application thereof

Through the multi-layer active layer structure design and material selection, the lithium ion diffusion rate and transmission path are optimized, which solves the shortcomings of traditional negative electrode sheets in terms of energy density, fast charging capacity and cycle stability, and achieves high energy density, fast charging capacity and excellent cycle performance.

CN120565579AActive Publication Date: 2025-08-29JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD

Patent Information

Application Number
CN202510660463.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-21
Publication Date
2025-08-29
Estimated Expiration
2045-05-21

AI Technical Summary

Technical Problem

The single active layer structure of the traditional negative electrode sheet cannot take into account the battery energy density, fast charging capacity and cycle stability, and there are problems such as the contradiction between energy density and fast charging performance, limited cycle life and insufficient interface stability.

Method used

The multi-layer active layer structure design is adopted. The first active layer close to the current collector is carbon-coated secondary particle graphite, the intermediate layer is heteroatom-doped hard carbon, and the third active layer far from the current collector is porous carbon nanofiber. The lithium ion diffusion rate and transmission path are optimized through the synergy of the materials of each layer.

Benefits of technology

It realizes the high energy density, fast charging capability and excellent circulation performance of lithium-ion batteries, inhibits the growth of lithium dendrites, and improves the battery cycle stability and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120565579A_ABST
    Figure CN120565579A_ABST
Patent Text Reader

Abstract

The invention relates to a negative pole piece and a preparation method and application thereof.The negative pole piece comprises a current collector and a negative active layer arranged on at least one face of the current collector in the thickness direction, the negative active layer comprises a first active layer, a second active layer and a third active layer, the first active layer is attached to the surface of the current collector, and the second active layer is attached to the surface of the current collector; the second active layer is arranged on the surface, far away from the current collector, of the first active layer, and the third active layer is arranged on the surface, far away from the first active layer, of the second active layer; the first active layer comprises carbon-coated secondary particle graphite, the second active layer comprises heteroatom-doped hard carbon, and the third active layer comprises porous carbon nanofibers. According to the lithium ion battery, the multiple active layers containing different active materials are arranged on the surface of the current collector, and meanwhile, the thickness of each active layer is regulated and the preparation process is optimized, so that the lithium ion battery containing the negative pole piece has high energy density, quick charge capacity and excellent cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a negative electrode plate and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries, due to their high energy density, long cycle life, and environmentally friendly features, have become a core energy device for electric vehicles, consumer electronics, and energy storage systems. As a key component of lithium-ion batteries, the performance of the anode directly affects the battery's energy density, fast charging capability, and cycle stability.

[0003] Traditional negative electrode plates usually adopt a single active layer structure, which is composed of active materials such as graphite and silicon-based materials, conductive agents and binders. However, this homogenized design cannot take into account the battery energy density, fast charging capability and cycle stability. It has the following problems: (1) The contradiction between energy density and fast charging performance: high active material content can improve energy density, but it will increase the lithium ion diffusion resistance and limit the fast charging capability. Although reducing the active material content improves the rate performance, it sacrifices energy density. Therefore, it is difficult to achieve both high energy density and fast charging capability; (2) Limited cycle life: under fast charging or high load conditions, the single active layer structure is prone to lithium dendrite growth, particle pulverization or interface side reactions, resulting in capacity decay; (3) Insufficient interface stability: in order to improve the battery energy density, the negative electrode active material contains silicon-based materials with high theoretical capacity, but such materials expand greatly during the charge and discharge process. During long-term cycle charge and discharge, mechanical stress is easily generated between the current collector and the active layer due to the difference in expansion coefficient, resulting in stratification and increased internal resistance.

[0004] Based on this, there is an urgent need to provide a negative electrode sheet that can take into account the battery energy density, fast charging capability and cycle stability, so as to meet the high performance requirements of lithium-ion batteries in terms of fast charging, long battery life and long life. Summary of the Invention

[0005] To solve the above problems, the present invention provides a negative electrode plate and its preparation method and application. Through the design of a multi-layer active layer structure and the selection of negative electrode active materials in each active layer, under the synergistic effect of the two, the lithium-ion battery containing the negative electrode plate can have high energy density, fast charging capability and excellent cycle performance.

[0006] Specifically, the following technical solutions are provided:

[0007] A first aspect of the present invention provides a negative electrode plate, comprising a current collector and a negative electrode active layer disposed on at least one side of the current collector along a thickness direction, wherein the negative electrode active layer comprises a first active layer, a second active layer, and a third active layer;

[0008] The first active layer is in contact with the surface of the current collector, the second active layer is arranged on the surface of the first active layer away from the current collector, and the third active layer is arranged on the surface of the second active layer away from the first active layer;

[0009] The first active layer comprises carbon-coated secondary graphite particles; the second active layer comprises hard carbon doped with heteroatoms, wherein the heteroatoms include one or more of B, N, O, P, S, F, and Cl; and the third active layer comprises porous carbon nanofibers.

[0010] Furthermore, the thickness ratio of the first active layer, the second active layer and the third active layer is (6-8): (1-2): (1-2), for example, 6:2:2, 7:2:1, 7:1:2, 8:1:1; that is, the thickness of the first active layer accounts for 60%-80% of the total thickness of the negative electrode active layer, the thickness of the second active layer accounts for 10%-20% of the total thickness of the negative electrode active layer, and the thickness of the third active layer accounts for 10%-20% of the total thickness of the negative electrode active layer.

[0011] Furthermore, the length of the porous carbon nanofiber is preferably 3-8 μm, and the diameter is preferably 100-500 nm.

[0012] Furthermore, the mass fraction of heteroatoms in the heteroatom-doped hard carbon is preferably 0.1%-1%.

[0013] Furthermore, the particle size D50 of the carbon-coated secondary graphite particles is preferably 10-18 μm.

[0014] A second aspect of the present invention provides a method for preparing the negative electrode sheet according to the first aspect, comprising the following steps:

[0015] S1, mixing the carbon-coated secondary graphite particles with a first conductive agent, a first binder, a first thickener, and a first solvent to obtain a first negative electrode active slurry;

[0016] uniformly mixing the heteroatom-doped hard carbon with a second conductive agent, a second binder, a second thickener, and a second solvent to obtain a second negative electrode active slurry;

[0017] uniformly mixing the porous carbon nanofibers with a third conductive agent, a third binder, a third thickener, and a third solvent to obtain a third negative electrode active slurry;

[0018] S2. Coating the first negative electrode active slurry, the second negative electrode active slurry and the third negative electrode active slurry on the surface of the current collector in sequence, and drying them to obtain the negative electrode sheet.

[0019] Furthermore, in step S1, the mass proportion of the carbon-coated secondary graphite particles in the first negative electrode active slurry is less than the mass proportion of the heteroatom-doped hard carbon in the second negative electrode active slurry is less than the mass proportion of the porous carbon nanofibers in the third negative electrode active slurry; the mass proportion of the carbon-coated secondary graphite particles in the first negative electrode active slurry is 96.0%-97.0%; the mass proportion of the heteroatom-doped hard carbon in the second negative electrode active slurry is 96.5%-97.5%; and the mass proportion of the porous carbon nanofibers in the third negative electrode active slurry is 97.5%-98%.

[0020] Further, in step S1, the mass proportion of the first binder in the first negative electrode active slurry is greater than the mass proportion of the second binder in the second negative electrode active slurry, and the mass proportion of the third binder in the third negative electrode active slurry; more preferably, the mass proportion of the first binder in the first negative electrode active slurry is 0.8%-2%; the mass proportion of the second binder in the second negative electrode active slurry is 0.5%-1.5%; and the mass proportion of the third binder in the third negative electrode active slurry is 0.2%-1.0%.

[0021] Further, in step S1, the viscosity of the first negative electrode active slurry is greater than the viscosity of the second negative electrode active slurry and greater than the viscosity of the third negative electrode active slurry; more preferably, the viscosity of the first negative electrode active slurry is 4000-5000 mPa·s; the viscosity of the second negative electrode active slurry is 3000-4000 mPa·s; and the viscosity of the third negative electrode active slurry is 2500-3500 mPa·s.

[0022] Furthermore, in step S1 , the solid contents of the first negative electrode active slurry, the second negative electrode active slurry and the third negative electrode active slurry are all 45%-55%.

[0023] Furthermore, in step S1, the carbon-coated secondary graphite particles are obtained by granulating and carbon-coating the primary graphite particles; specifically: the primary graphite particles are granulated to obtain secondary graphite particles, which are then evenly mixed with a carbon precursor and placed in an inert atmosphere for carbonization treatment to obtain the carbon-coated secondary graphite particles.

[0024] Wherein, the primary graphite particles include primary artificial graphite particles and / or primary natural graphite particles; preferably, the primary artificial graphite particles include one or more of needle coke, petroleum coke, pitch coke and mesophase carbon microbeads, and the primary natural graphite particles include flake graphite and / or microcrystalline graphite;

[0025] The carbon precursor (precursor used for carbon coating) includes one or more of coal tar pitch, petroleum pitch, coal liquefaction pitch, ethylene tar pitch, natural asphalt, anthracite, mesophase carbon microbeads, coconut shell, cotton, tree, glucose, lignin, cellulose, phenolic resin, polyaniline and polyacrylonitrile.

[0026] Furthermore, in step S1, the preparation of the heteroatom-doped hard carbon includes the following steps: uniformly mixing a hard carbon source and a heteroatom dopant, and then performing a carbonization treatment under an inert atmosphere to obtain the heteroatom-doped hard carbon.

[0027] Wherein, the hard carbon source includes one or more of coconut shell, cotton, tree, glucose, lignin, cellulose, phenolic resin, polyaniline and polyacrylonitrile;

[0028] The heteroatom dopant includes one or more of borane, borax, boron tetrachloride, urea, ammonium chloride, ammonium sulfate, ammonium dihydrogen phosphate, elemental sulfur, thiourea, polyvinylidene fluoride, ammonium hexafluorophosphate, and potassium hexafluorophosphate;

[0029] The mass ratio of the hard carbon source to the dopant is preferably 10:(1-5);

[0030] The carbonization temperature is preferably 1200-1800° C., and the carbonization time is preferably 1-5 hours.

[0031] Furthermore, in step S1, the porous carbon nanowire fibers are firstly crushed and then mixed with a third conductive agent, a third binder, a third thickener and a third solvent to prepare a third negative electrode active slurry.

[0032] Furthermore, the preparation of the porous carbon nanofibers comprises the following steps:

[0033] (1) mixing phenolic resin, polyacrylonitrile, zinc salt and solvent to obtain a spinning solution;

[0034] (2) subjecting the spinning solution prepared in step (1) to electrospinning to obtain a raw silk fiber material;

[0035] (3) The raw fiber material prepared in step (2) is carbonized under an inert atmosphere to obtain the porous carbon nanofiber.

[0036] Furthermore, in step (1), the zinc salt includes one or more of zinc nitrate, zinc chloride, zinc oxide, and zinc phytate; and the solvent is N,N-dimethylformamide.

[0037] Furthermore, in step (1), the mixing treatment step is carried out under oil bath heating conditions, the oil bath heating temperature is 40-80° C., and the oil bath heating time is 1-10 h.

[0038] Furthermore, in step (1), the mass proportion of zinc salt in the spinning solution is preferably 0.5%-1.5%.

[0039] Furthermore, in step (2), in the electrospinning treatment step: the injection rate is preferably 0.5-1.2 mL / min, the voltage is preferably 16-20 KV, the temperature is preferably 20-25° C., and the humidity is preferably 20%-40%.

[0040] Furthermore, in step (3), the temperature of the carbonization treatment is preferably 1000-1500° C., and the time of the carbonization treatment is preferably 1-5 h.

[0041] A third aspect of the present invention provides a lithium-ion battery comprising the negative electrode sheet described in the first aspect or the negative electrode sheet prepared by the preparation method described in the second aspect.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] The present invention provides a negative electrode plate with a three-layer active layer structure design, wherein the first active layer close to the current collector uses carbon-coated secondary graphite particles as the active material, the middle second active layer uses hard carbon doped with heteroatoms as the active material, and the third active layer away from the current collector uses porous carbon nanofibers as the active material, so that the diffusion rate of lithium ions in the negative electrode plate shows a step-by-step decreasing trend from one end close to the diaphragm to the other end of the current collector, and through the selection of specific negative electrode active materials in each layer, a suitable gradient change of the lithium ion diffusion rate in the negative electrode active layer can be achieved, which not only realizes the rapid diffusion and transmission of lithium ions and improves the fast charging performance, but also helps to inhibit the growth of lithium dendrites and improve the battery cycle stability; in addition, the above-mentioned multi-layer gradient design allows the increase of the active material load without significantly sacrificing the rate performance by optimizing the transmission path, thereby helping to improve the energy density; so that the lithium-ion battery can have high energy density, fast charging capability and excellent cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a schematic structural diagram of a negative electrode sheet of the present invention;

[0045] In the figure: 1 is the current collector, 21 is the first active layer, 22 is the second active layer, and 23 is the third active layer. DETAILED DESCRIPTION

[0046] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention pertains. The terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the relevant listed items. The term "includes" or "comprising" described in the present invention means that in addition to the components described, it may also include or contain other components. The term "includes" or "comprising" described in the present invention may also be replaced by the closed form "for" or "consisting of..."

[0047] As mentioned in the background, current negative electrode plates typically utilize a single active layer structure, consisting of active materials such as graphite and silicon-based materials, a conductive agent, and a binder. However, this homogenized design fails to balance battery energy density, fast-charging capability, and cycling stability, and thus fails to meet the high-performance requirements of lithium-ion batteries for fast charging, long battery life, and other aspects.

[0048] To solve the above problems, the embodiments of the present invention provide a negative electrode plate, which includes a current collector and a negative electrode active layer provided on at least one side of the current collector along the thickness direction, wherein the negative electrode active layer includes a first active layer, a second active layer and a third active layer; wherein,

[0049] The first active layer is in contact with the surface of the current collector, and the first active layer comprises carbon-coated secondary graphite particles; using carbon-coated secondary graphite particles as the active material of the first active layer (bottom layer) can significantly increase the diffusion rate of lithium ions and reduce the charging time of the lithium ion battery. Specifically: (1) the secondary graphite particles have high isotropy, which is conducive to the insertion and extraction of lithium ions in all directions; (2) the modification treatment of the carbon coating can increase the diffusion rate of lithium ions in the coating layer;

[0050] The second active layer is arranged on the surface of the first active layer away from the current collector, and the first active layer comprises carbon-coated secondary graphite particles; the second active layer comprises hard carbon doped with heteroatoms, and the heteroatoms include one or more of B, N, O, P, S, F, and Cl; the use of heteroatom-doped hard carbon materials as the active material of the second active layer (middle layer) has at least the following advantages: (1) the hard carbon material has a large interlayer spacing, which can greatly increase the diffusion rate of lithium ions in the material; (2) the interlayer spacing of the hard carbon material can be further increased by the method of heteroatom doping; at the same time, the doping of heteroatoms will introduce some pore structures into the material, and the existence of the pore structure can serve as a channel for rapid transmission of lithium ions. The significant increase in the lithium ion diffusion rate will shorten the charging time of the lithium ion battery; (3) as a connection between the bottom layer and the top layer, the diffusion rate of lithium ions in the middle layer is between the top layer and the bottom layer, playing a transition role, reducing the diffusion rate gradient of lithium ions, which is conducive to reducing the generation of lithium ion diffusion stress and reducing the risk of falling off of each coating layer;

[0051] The third active layer is arranged on the surface of the second active layer away from the first active layer; the third active layer contains porous carbon nanofibers; using porous carbon nanofibers as the active material of the third active layer (upper layer) has the following advantages: (1) carbon nanofibers have excellent electrical conductivity and can effectively improve the charge and discharge rate and overall performance of the battery; (2) the larger specific surface area of ​​carbon nanofibers helps to increase the contact area between the electrode and the electrolyte, improve the transmission efficiency of lithium ions, and thus improve the capacity and rate performance of the battery; (3) the unique nanostructure of carbon nanofibers provides a fast transmission channel for lithium ions, which helps to improve the rate performance of the battery; (4) the unique pore structure in porous carbon nanofibers can serve as a channel for the rapid transmission of lithium ions, greatly improving the diffusion rate of lithium ions.

[0052] Based on the fact that the homogenized design of existing negative electrode sheets cannot take into account the battery energy density, fast charging capability and cycle stability, the present invention, through the design of a multi-layer active layer structure and the selection of negative electrode active materials in each active layer, under the synergistic effect of structure and materials, enables a lithium-ion battery containing the above-mentioned negative electrode sheet to take into account energy density, fast charging capability and cycle performance. Specifically: The present invention provides a negative electrode sheet with a three-layer active layer structure design, wherein the first active layer close to the current collector uses carbon-coated secondary graphite particles as the active material, the middle second active layer uses heteroatom-doped hard carbon as the active material, and the third active layer away from the current collector uses porous carbon nanofibers as the active material. The diffusion rate of lithium ions in these active materials is as follows: porous carbon nanofibers > heteroatom-doped hard carbon > carbon-coated secondary graphite particles, that is, the diffusion rate of lithium ions in the negative electrode sheet shows a step-by-step decreasing trend from the end close to the separator to the end of the current collector, and the selection of specific negative electrode active materials in each layer can achieve a suitable gradient change in the lithium ion diffusion rate within the negative electrode active layer. Through the synergistic effect of the above structural design and material selection, the prepared negative electrode sheet has at least the following advantages:

[0053] (1) Optimize lithium ion transfer kinetics, reduce concentration polarization, and improve fast charging performance: The area close to the diaphragm has a high diffusion rate, which can quickly respond to the lithium ion demand in the electrolyte and reduce ion accumulation at the interface; while the area close to the current collector diffuses slowly, matching the electron conduction speed and avoiding local lithium ion shortage; thus, it can reduce concentration polarization and improve rate performance.

[0054] (2) It is beneficial to inhibit the growth of lithium dendrites and improve the cycle stability and safety of batteries: the high diffusion rate area (diaphragm side) can quickly replenish lithium ions, avoid local excessive deposition of lithium ions to form lithium dendrites, and prevent lithium dendrites from piercing the diaphragm and causing thermal runaway. In addition, a suitable gradient distribution of diffusion rate can guide lithium ions to be more uniformly embedded / ejected. For example, heteroatom-doped hard carbon is used as the active material of the intermediate layer. After heteroatom doping, the spacing between the hard carbon layers is increased and a pore structure is introduced. The expansion of the interlayer spacing and the existence of the pore structure make the diffusion rate of lithium ions in the heteroatom-doped hard carbon material second only to that of porous carbon nanofibers. The intermediate layer is used as the connection between the bottom layer and the top layer, which can reduce the diffusion rate gradient of lithium ions, which is beneficial to reduce the generation of lithium ion diffusion stress, thereby reducing the risk of each coating layer falling off, and further improving the cycle stability of the battery.

[0055] (3) Compatible with high energy density: The gradient design improves the fast charging performance of the electrode by optimizing the transmission path, allowing the active material loading to be increased without significantly sacrificing the battery energy density.

[0056] In the present invention, in order to maintain the gram capacity of the electrode and effectively improve the overall fast charging performance of the electrode, the thickness ratio of the first active layer, the second active layer and the third active layer is preferably (6-8): (1-2): (1-2), for example 6:2:2, 7:2:1, 7:1:2, 8:1:1, etc., including but not limited to the thickness ratios listed above; that is, the thickness of the first active layer accounts for 60%-80% of the total thickness of the negative electrode active layer, the thickness of the second active layer accounts for 10%-20% of the total thickness of the negative electrode active layer, and the thickness of the third active layer accounts for 10%-20% of the total thickness of the negative electrode active layer.

[0057] In the present invention, the length of the porous carbon nanofibers is preferably 3-8 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, etc., and the diameter is preferably 100-500 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, etc., including but not limited to the above-listed values. The present invention controls the length and diameter of the porous carbon nanofibers within the above-mentioned range, which is beneficial to further promote the rapid migration of lithium ions and improve the fast charging capability of lithium-ion batteries.

[0058] In the present invention, heteroatom doping of hard carbon can increase the interlayer spacing of the hard carbon. A larger interlayer spacing facilitates the rapid diffusion of lithium ions. Heteroatom doping can also improve the conductivity of the material and enhance the rapid transport of electrons and ions. Furthermore, heteroatom doping can create a pore structure in the material, which can serve as a channel for the rapid transport of lithium ions, accelerating the transport of lithium ions. However, heteroatom doping can also introduce some defects. The formation of the pore structure increases the specific surface area of ​​the material. These defects and the increase in specific surface area increase lithium ion consumption, reducing the cycle life of the battery. Therefore, while minimizing the loss of cycle life, the migration rate of lithium ions is increased to improve the fast charging capability of lithium-ion batteries. Preferably, the mass fraction of heteroatoms in the heteroatom-doped hard carbon is controlled within the range of 0.1% to 1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc., including but not limited to the mass fractions listed above.

[0059] In the present invention, the particle size D50 of the carbon-coated secondary graphite particles is preferably 10-18 μm, for example, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, etc., including but not limited to the particle sizes listed above. Controlling the particle size D50 of the carbon-coated secondary graphite particles within the range of 10-18 μm can ensure that the secondary particles have a high degree of granulation and have a high isotropy, which is conducive to the embedding and extraction of lithium ions in all directions.

[0060] The present invention also provides a method for preparing the negative electrode sheet, which includes the following steps:

[0061] S1, mixing the carbon-coated secondary graphite particles with a first conductive agent, a first binder, a first thickener, and a first solvent to obtain a first negative electrode active slurry;

[0062] uniformly mixing the heteroatom-doped hard carbon with a second conductive agent, a second binder, a second thickener, and a second solvent to obtain a second negative electrode active slurry;

[0063] uniformly mixing the porous carbon nanofibers with a third conductive agent, a third binder, a third thickener, and a third solvent to obtain a third negative electrode active slurry;

[0064] S2. Coating the first negative electrode active slurry, the second negative electrode active slurry and the third negative electrode active slurry on the surface of the current collector in sequence, and drying them to obtain the negative electrode sheet.

[0065] In step S1 of the present invention, the mass proportion of the carbon-coated secondary graphite particles in the first negative electrode active slurry is < the mass proportion of the heteroatom-doped hard carbon in the second negative electrode active slurry is < the mass proportion of the porous carbon nanofibers in the third negative electrode active slurry; the mass proportion of the first binder in the first negative electrode active slurry is > the mass proportion of the second binder in the second negative electrode active slurry is > the mass proportion of the third binder in the third negative electrode active slurry.

[0066] Since the binder floats during the drying process of the electrode, the proportion of active material in the first to third negative electrode active slurries prepared by the present invention gradually decreases, and the proportion of binder gradually increases, so that the binder can be evenly distributed in each layer of the electrode after drying, avoiding the occurrence of active material shedding, which is beneficial to improving the cycle performance of the lithium-ion battery.

[0067] More preferably, the mass proportion of the carbon-coated secondary graphite particles in the first negative electrode active slurry is 96.0%-97.0%, for example, 96.0%, 96.5%, 97%, etc.; the mass proportion of the heteroatom-doped hard carbon in the second negative electrode active slurry is 96.5%-97.5%, for example, 96.5%, 97%, 97.5%, etc.; the mass proportion of the porous carbon nanofiber in the third negative electrode active slurry is 97.5%-98%, for example, 97.5%, 98%, etc.; the mass proportion of the first binder in the first negative electrode active slurry is 0.8%-2%, for example, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, etc.; the mass proportion of the second binder in the second negative electrode active slurry is 0.5%-1.5%, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, etc.; the mass proportion of the third binder in the third negative electrode active slurry is 0.2%-1.0%, for example, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc., including but not limited to the mass proportions listed above.

[0068] In some preferred embodiments of the present invention, in step S1, the mass ratio of carbon-coated secondary particle graphite to the first conductive agent, the first binder, and the first thickener is (96.0-97.0): (0.7-1.5): (0.8-2): (0.6-1.5); the mass ratio of heteroatom-doped hard carbon to the second conductive agent, the second binder, and the second thickener is (96.5-97.5): (0.7-1.5): (0.5-1.5): (0.4-1.0); the mass ratio of porous carbon nanofibers to the third conductive agent, the third binder, and the third thickener is (97.5-98.0): (0.7-1.5): (0.2-1.0): (0.2-0.8).

[0069] In step S1 of the present invention, the viscosity of the first negative electrode active slurry is greater than the viscosity of the second negative electrode active slurry, and the viscosity of the third negative electrode active slurry is greater than that of the third negative electrode active slurry. Since the bottom membrane surface absorbs the solvent of the slurry during multiple coating processes, the slurry is not easy to level, which in turn causes leakage of the bottom membrane surface. By adjusting the discharge viscosity of the slurry to decrease in sequence, the above-mentioned undesirable phenomenon can be avoided.

[0070] More preferably, the viscosity of the first negative electrode active slurry is 4000-5000 mPa·s, such as 4000 mPa·s, 4200 mPa·s, 4400 mPa·s, 4600 mPa·s, 4800 mPa·s, 5000 mPa·s, etc.; the viscosity of the second negative electrode active slurry is 3000-4000 mPa·s, such as 3000 mPa·s, 3200 mPa·s, 3400 mPa·s, 3600 mPa·s, 3800 mPa·s, etc. Pa·s, 4000mPa·s, etc.; the viscosity of the third negative electrode active slurry is 2500-3500mPa·s, for example, 2500mPa·s, 2600mPa·s, 2700mPa·s, 2800mPa·s, 2900mPa·s, 3000mPa·s, 3100mPa·s, 3300mPa·s, 3300mPa·s, 3400mPa·s, 3500mPa·s, etc., including but not limited to the viscosity values ​​listed above.

[0071] In step S1 of the present invention, the solid contents of the first negative electrode active slurry, the second negative electrode active slurry, and the third negative electrode active slurry are all 45%-55%, such as 45%, 50%, 55%, etc.

[0072] In some preferred embodiments of the present invention, in step S1, the carbon-coated secondary graphite particles are obtained by granulating and carbon-coating primary graphite particles; specifically: the primary graphite particles are granulated to obtain secondary graphite particles, which are then evenly mixed with a carbon precursor and placed in an inert atmosphere for carbonization treatment to obtain the carbon-coated secondary graphite particles.

[0073] Preferably, the primary graphite particles include primary artificial graphite particles and / or primary natural graphite particles; the primary artificial graphite particles include one or more of needle coke, petroleum coke, pitch coke and mesophase carbon microbeads, and the primary natural graphite particles include flake graphite and / or microcrystalline graphite.

[0074] Preferably, the carbon precursor (precursor used for carbon coating) includes one or more of coal tar pitch, petroleum pitch, coal liquefaction pitch, ethylene tar pitch, natural asphalt, anthracite, mesophase carbon microbeads, coconut shell, cotton, tree, glucose, lignin, cellulose, phenolic resin, polyaniline and polyacrylonitrile.

[0075] In some preferred embodiments of the present invention, in step S1, the preparation of the heteroatom-doped hard carbon includes the following steps: uniformly mixing a hard carbon source and a heteroatom dopant, and then carbonizing the mixture under an inert atmosphere to obtain the heteroatom-doped hard carbon.

[0076] Preferably, the hard carbon source includes one or more of coconut shell, cotton, tree, glucose, lignin, cellulose, phenolic resin, polyaniline and polyacrylonitrile; the heteroatom dopant includes one or more of borane, borax, boron tetrachloride, urea, ammonium chloride, ammonium sulfate, diammonium dihydrogen phosphate, elemental sulfur, thiourea, polyvinylidene fluoride, ammonium hexafluorophosphate, and potassium hexafluorophosphate.

[0077] Preferably, the mass ratio of the hard carbon source to the dopant is preferably 10:(1-5), such as 10:1, 10:2, 10:3, 10:4, 10:5, etc., including but not limited to the mass ratios listed above.

[0078] Preferably, the carbonization temperature is preferably 1200-1800°C, such as 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C, etc., and the carbonization time is preferably 1-5h, such as 1h, 2h, 3h, 4h, 5h, etc.

[0079] In some preferred embodiments of the present invention, in step S1, the porous carbon nanowire fibers are firstly crushed and then mixed with a third conductive agent, a third binder, a third thickener, and a third solvent to prepare a third negative electrode active slurry.

[0080] In some preferred embodiments of the present invention, in step S1, the preparation of the porous carbon nanofibers comprises the following steps:

[0081] (1) mixing phenolic resin, polyacrylonitrile, zinc salt and solvent to obtain a spinning solution;

[0082] (2) subjecting the spinning solution prepared in step (1) to electrospinning to obtain a raw silk fiber material;

[0083] (3) The raw fiber material prepared in step (2) is carbonized under an inert atmosphere to obtain the porous carbon nanofiber.

[0084] Preferably, in step (1), the zinc salt includes one or more of zinc nitrate, zinc chloride, zinc oxide, and zinc phytate; and the solvent includes but is not limited to N,N-dimethylformamide.

[0085] Preferably, in step (1), the mixing treatment step is carried out under oil bath heating conditions, the oil bath heating temperature is 40-80°C, and the oil bath heating time is 1-10 hours, for example, oil bath heating is carried out at 60°C for 5 hours.

[0086] Preferably, in step (1), the mass proportion of zinc salt in the spinning solution is 0.5%-1.5%, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, etc., including but not limited to the mass proportions listed above; in some preferred embodiments of the present invention, the mass ratio of phenolic resin to polyacrylonitrile, zinc salt, and solvent is 4.5%:10.5%:1%:84%.

[0087] Preferably, in step (2), in the electrospinning treatment step: the injection rate is preferably 0.5-1.2 mL / min, the voltage is preferably 16-20 KV, the temperature is preferably 20-25° C., and the humidity is preferably 20%-40%.

[0088] Preferably, in step (3), the temperature of the carbonization treatment is preferably 1000-1500°C, for example, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, etc., and the time of the carbonization treatment is preferably 1-5h, for example, 1h, 2h, 3h, 4h, 5h, etc.

[0089] In addition, the embodiments of the present invention also provide a lithium-ion battery comprising a negative electrode sheet prepared by the above method, which is charged and discharged under high rate conditions, can not only effectively suppress lithium plating, but also have high energy density and excellent cycle performance.

[0090] Example 1

[0091] This embodiment relates to the preparation of a negative electrode sheet, and the specific operations are as follows:

[0092] Preparation of carbon-coated secondary graphite particles: Microcrystalline graphite was used as the raw material and granulated to obtain secondary graphite particles. The secondary graphite particles were then carbon-coated (temperature: 1100°C, holding time: 3 hours) using coal tar pitch as a coating agent (mass ratio of coating agent to secondary graphite particles: 1:20) to obtain a carbon-coated secondary graphite material with a D50 of 14 μm.

[0093] Preparation of heteroatom-doped hard carbon: 10g of a mixture of phenolic resin and polyacrylonitrile (the mass ratio of phenolic resin to polyacrylonitrile is 6:4) was ground and mixed with 4g of elemental sulfur. The mixture was then heated to 1600°C at a rate of 3°C / min under an inert atmosphere and held at that temperature for 3h. After cooling, a sulfur-doped hard carbon material was obtained with a sulfur doping level of 0.4%.

[0094] Preparation of porous carbon nanofibers:

[0095] The solvent DMF (N,N-dimethylacetamide), the spinning aid PAN (polyacrylonitrile), the phenolic resin and the zinc chloride were mixed in a ratio of 84%:10.5%:4.5%:1%, and then heated in an oil bath at 60°C for 5 hours to obtain a spinning solution;

[0096] The prepared spinning solution was drawn into the syringe, connected to the needle, and connected to the electrospinning device. The injection speed was adjusted to 0.8 mL / min, the voltage was 18 KV, the temperature was 23 ° C, and the humidity was 30% to perform electrospinning to obtain the raw silk fiber material;

[0097] The raw fiber material was heated to 1300° C. at a heating rate of 3° C. / min under an inert protective atmosphere, kept warm for 3 hours, carbonized, and cooled automatically to obtain porous carbon nanofibers.

[0098] Preparation of negative electrode active slurry:

[0099] The carbon-coated secondary graphite particles prepared above were dry-mixed with conductive carbon black. A binder (CMCC, sodium carboxymethyl cellulose) and a thickener (SBR, styrene-butadiene rubber) were then added, followed by stirring until uniformly mixed. This prepared a first negative electrode active slurry. The weight ratio of the carbon-coated secondary graphite particles, conductive carbon black, binder, and thickener was 96.3:1.0:1.2:1.5. The first negative electrode active slurry had a viscosity of 4400 mPa·s and a solids content of 50.1%.

[0100] The heteroatom-doped hard carbon material prepared above was dry-mixed with conductive carbon black. A binder (CMCC), a thickener (SBR), and deionized water were then added and stirred to form a second negative electrode active slurry. The weight ratio of the heteroatom-doped hard carbon, conductive carbon black, binder, and thickener was 96.9:1.0:1.3:0.8. The viscosity of the second negative electrode active slurry was 3250 mPa·s, and the solids content was 50.5%.

[0101] The porous carbon nanofibers prepared above were pulverized and then dry-mixed with conductive carbon black. A binder (CMCC), a thickener (SBR), and deionized water were then added and stirred to form a third negative electrode active slurry. The weight ratio of the heteroatom-doped hard carbon, conductive carbon black, binder, and thickener was 97.6:1.2:0.7:0.5. The viscosity of the third negative electrode active slurry was 3240 mPa·s, and the solids content was 50.3%.

[0102] Coating: Using a three-layer coating machine, the first negative electrode active slurry is applied to the surface of the current collector. The second negative electrode active slurry is applied to the surface of the first negative electrode active slurry. The third negative electrode active slurry is applied to the surface of the second negative electrode active slurry. The mixture is then dried to obtain a three-layer coated negative electrode sheet. The thickness ratio of the first active layer, the second active layer, and the third active layer is 6:2:2.

[0103] The active layers of the negative electrode prepared in this embodiment are, from the inside to the outside, a carbon-coated secondary granular graphite layer (first active layer), a heteroatom-doped hard carbon layer (second active layer), and a porous carbon nanofiber layer (third active layer).

[0104] Examples 2-6

[0105] Examples 2-6 all involve the preparation of a negative electrode sheet. The difference from Example 1 is the preparation of carbon-coated secondary graphite particles, heteroatom-doped hard carbon, and porous carbon nanofibers, as well as the preparation of the first negative electrode active slurry, the second negative electrode active slurry, and the third negative electrode active slurry. The remaining operations are the same; the details are shown in Tables 1-6 below:

[0106] Table 1

[0107]

[0108] Table 2

[0109]

[0110] Table 3

[0111]

[0112] Table 4

[0113]

[0114] Table 5

[0115]

[0116] Table 6

[0117]

[0118] Example 7

[0119] Example 7 relates to the preparation of a negative electrode plate, which differs from Example 1 in that: the ratio of the active layer thickness. The active layer of the negative electrode plate prepared in this example is, from the inside to the outside, a carbon-coated secondary granular graphite layer, a heteroatom-doped hard carbon layer, and a porous carbon nanofiber layer. The coating thickness ratio of the carbon-coated secondary granular graphite layer to the heteroatom-doped hard carbon layer and the porous carbon nanofiber layer is 2:4:4.

[0120] Comparative Example 1

[0121] Comparative Example 1 relates to the preparation of a negative electrode sheet, which differs from Example 1 in that: the coating order, specifically, a third negative electrode active slurry is coated on the surface of the current collector through a three-layer coating machine, a second negative electrode active slurry is coated on the surface of the third negative electrode active slurry, and a first negative electrode active slurry is coated on the surface of the second negative electrode active slurry, and it is dried to obtain a three-layer coated negative electrode sheet.

[0122] The active layers of the negative electrode plate prepared in this comparative example are, from the inside to the outside, a porous carbon nanofiber layer, a heteroatom-doped hard carbon layer, and a carbon-coated secondary particle graphite layer. The coating thickness ratio of the porous carbon nanofiber layer to the heteroatom-doped hard carbon layer and the carbon-coated secondary particle graphite layer is 2:2:6.

[0123] Comparative Example 2

[0124] Comparative Example 2 involves the preparation of a negative electrode sheet, which differs from Example 1 in that: the coating order, specifically, the third negative electrode active slurry is coated on the surface of the current collector through a three-layer coating machine, the first negative electrode active slurry is coated on the surface of the third negative electrode active slurry, and the second negative electrode active slurry is coated on the surface of the first negative electrode active slurry, and it is dried to obtain a three-layer coated negative electrode sheet.

[0125] The active layers of the negative electrode plate prepared in this comparative example are, from the inside to the outside, a porous carbon nanofiber layer, a carbon-coated secondary particle graphite layer, and a heteroatom-doped hard carbon layer. The coating thickness ratio of the porous carbon nanofiber layer to the carbon-coated secondary particle graphite layer and the heteroatom-doped hard carbon layer is 2:6:2.

[0126] Comparative Example 3

[0127] Comparative Example 3 relates to the preparation of a negative electrode plate, which differs from Example 1 in that: the second negative electrode active material, specifically, the second negative electrode active material is a soft carbon material doped with heteroatoms, and the carbon source precursor is changed from a mixture of 10g of phenolic resin and polyacrylonitrile (6:4) to 10g of coal tar pitch, and the other substances are not changed.

[0128] The active layers of the negative electrode plate prepared in this comparative example are, from the inside to the outside, a carbon-coated secondary particle graphite layer, a heteroatom-doped soft carbon layer and a porous carbon nanofiber layer. The coating thickness ratio of the carbon-coated secondary particle graphite layer to the heteroatom-doped soft carbon layer and the porous carbon nanofiber layer is 6:2:2.

[0129] Application and performance testing

[0130] The negative electrode sheets prepared in the above examples and comparative examples were used to construct lithium-ion soft-pack batteries, as follows:

[0131] Preparation of positive electrode sheet: The positive electrode active material lithium iron phosphate, the conductive agent SP, and the binder polyvinylidene fluoride are fully stirred and mixed in an appropriate amount of N-methylpyrrolidone solvent in a weight ratio of 96.7:1.5:1.8 to form a uniform positive electrode slurry; this slurry is coated on the positive electrode current collector Al foil, dried, and cold pressed to obtain a positive electrode sheet.

[0132] Diaphragm: Use commercially available ceramic isolation membrane.

[0133] Electrolyte: Ethylene carbonate EC, diethyl carbonate DEC, and ethyl methyl carbonate EMC are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then solute LiPF6 is added to the organic solvent to dissolve and mix uniformly to obtain an electrolyte; wherein the concentration of LiPF6 is 1M.

[0134] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrodes to act as an isolate. Then they are wound and placed in outer packaging foil. After the battery cell is baked, the electrolyte injection and infiltration process can be carried out when the moisture content of the positive and negative electrodes is less than 200ppm to prepare a 2.8Ah soft-pack battery.

[0135] The following electrochemical performance tests were performed on the soft-pack batteries prepared with different negative electrode sheets:

[0136] Lithium plating test (10C direct charge 80% SOC): The 2.8Ah soft-pack battery is discharged at a constant current of 1C to 2.5V, and then charged at a constant current of 10C for 4.8 minutes, that is, charged to 80% SOC. The battery is then disassembled and the negative electrode is observed to see if there is lithium plating.

[0137] Cycling test: The 2.8Ah soft-pack battery was discharged at a constant current of 1C to 2.5V. It was then charged and discharged at a current of 4C, with the upper charge voltage limit at 3.65V and the lower discharge voltage limit at 2.5V. When the capacity retention rate dropped to 80%, the battery was removed from the production line, and the number of cycles at the time of removal was recorded. The soft-pack battery was disassembled after being removed from the production line to observe the shedding of active material from the anode electrode.

[0138] Capacity test (withholding charge): Use a punching machine to cut the negative electrode sheets of the above embodiments and comparative examples into 14.5mm electrode sheets. Then, use a lithium sheet as the counter electrode and use the above electrolyte and separator to perform constant current charge and discharge capacity tests at a current density of 0.01C. The charge and discharge voltage range is 0.01-2.5V, and its gram capacity is measured.

[0139] The test results are shown in Table 7 below:

[0140] Table 7

[0141]

[0142]

[0143] As shown in Table 7, the lithium-ion batteries constructed with the negative electrode sheets prepared in Examples 1-7 were charged to 80% SOC at a current of 10C, and no lithium plating was observed in the negative electrode sheets. Furthermore, under high-rate (4C) charge and discharge conditions, they maintained a long cycle life, with the number of cycles corresponding to a capacity drop to 80% being no less than 1192. However, in Comparative Examples 1 and 2, which only adjusted the order of the coatings and did not change the content of the active materials in the sheet, the prepared negative electrode sheets exhibited severe lithium plating under the same conditions. Furthermore, under high-rate conditions, the battery capacity dropped to below 80% after only less than 100 cycles of charge and discharge (due to polarization during the cycle, lithium plating occurred, the capacity plummeted, and the capacity retention rate quickly dropped below 80%). It can be seen from this that the coating order of each active layer not only has a great influence on the fast charging performance of the battery, but also affects the cycle life under high-rate conditions. When the diffusion rate of lithium ions in the negative electrode plate shows a step-by-step decreasing trend from the end close to the diaphragm to the end of the current collector, the lithium-ion battery not only has fast charging performance, but also has excellent cycle stability.

[0144] It can be seen from Example 1 and Comparative Example 3 that when a heteroatom-doped soft carbon material is used to replace the heteroatom-doped hard carbon material in the negative electrode plate of Example 1, lithium plating occurs in the lithium-ion battery, and the cycle life of charge and discharge at 4C is significantly reduced. In addition, compared with Example 1 and Comparative Example 1, the negative electrode plates prepared in Comparative Examples 2 and 3 all show active material shedding after the cycle test. This is because the span of the lithium ion diffusion rate between the coatings in the negative electrode plate is large, which generates large stress and causes the active material to fall off. It can be seen that by selecting specific negative electrode active materials for each layer, a suitable gradient change of the lithium ion diffusion rate in the negative electrode active layer is achieved, which is beneficial to improving the cycle performance of the battery.

[0145] In addition, it can be seen from Examples 1 and 7 that the thickness ratio of each active layer in the negative electrode plate will affect the gram capacity of the battery. When the content of graphite, which serves as the main capacity support, is only 20%, the gram capacity of the battery is significantly reduced. Therefore, in order to ensure the high gram capacity of the battery while having fast charging capability and excellent cycle performance, it is preferred that the thickness of each active layer in the negative electrode plate is controlled within a suitable range. For example, the layer thickness ratio of the first active layer to the second active layer and the third active layer is 6:2:2.

[0146] The above-described embodiments are merely preferred examples for the purpose of fully illustrating the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are within the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

Claims

1. A negative electrode plate, characterized in that: The negative electrode plate includes a current collector and a negative electrode active layer provided on at least one side of the current collector along the thickness direction, wherein the negative electrode active layer includes a first active layer, a second active layer and a third active layer; The first active layer is in contact with the surface of the current collector, the second active layer is arranged on the surface of the first active layer away from the current collector, and the third active layer is arranged on the surface of the second active layer away from the first active layer; The first active layer comprises carbon-coated secondary graphite particles; the second active layer comprises hard carbon doped with heteroatoms, wherein the heteroatoms include one or more of B, N, O, P, S, F, and Cl; and the third active layer comprises porous carbon nanofibers.

2. The negative electrode sheet according to claim 1, characterized in that: The thickness of the first active layer accounts for 60%-80% of the total thickness of the negative electrode active layer; the thickness of the second active layer accounts for 10%-20% of the total thickness of the negative electrode active layer; the thickness of the third active layer accounts for 10%-20% of the total thickness of the negative electrode active layer.

3. The negative electrode sheet according to claim 1, characterized in that: Contain at least one of the following characteristics: (1) The porous carbon nanofibers have a length of 3-8 μm and a diameter of 100-500 nm; (2) The mass fraction of heteroatoms in the heteroatom-doped hard carbon is 0.1% to 1%; (3) The particle size D50 of the carbon-coated secondary graphite particles is 10-18 μm.

4. A method for preparing a negative electrode sheet according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, mixing the carbon-coated secondary graphite particles with a first conductive agent, a first binder, a first thickener, and a first solvent to obtain a first negative electrode active slurry; uniformly mixing the heteroatom-doped hard carbon with a second conductive agent, a second binder, a second thickener, and a second solvent to obtain a second negative electrode active slurry; uniformly mixing the porous carbon nanofibers with a third conductive agent, a third binder, a third thickener, and a third solvent to obtain a third negative electrode active slurry; S2. Coating the first negative electrode active slurry, the second negative electrode active slurry and the third negative electrode active slurry on the surface of the current collector in sequence, and drying them to obtain the negative electrode sheet.

5. The preparation method according to claim 4, characterized in that The step S1 includes at least one of the following features: (1) The mass proportion of the carbon-coated secondary graphite particles in the first negative electrode active slurry is less than the mass proportion of the heteroatom-doped hard carbon in the second negative electrode active slurry and less than the mass proportion of the porous carbon nanofibers in the third negative electrode active slurry; the mass proportion of the carbon-coated secondary graphite particles in the first negative electrode active slurry is 96.0%-97.0%; the mass proportion of the heteroatom-doped hard carbon in the second negative electrode active slurry is 96.5%-97.5%; the mass proportion of the porous carbon nanofibers in the third negative electrode active slurry is 97.5%-98%; (2) The mass proportion of the first binder in the first negative electrode active slurry> the mass proportion of the second binder in the second negative electrode active slurry> the mass proportion of the third binder in the third negative electrode active slurry; preferably, the mass proportion of the first binder in the first negative electrode active slurry is 0.8%-2%; the mass proportion of the second binder in the second negative electrode active slurry is 0.5%-1.5%; the mass proportion of the third binder in the third negative electrode active slurry is 0.2%-1.0%; (3) The viscosity of the first negative electrode active slurry is greater than the viscosity of the second negative electrode active slurry and greater than the viscosity of the third negative electrode active slurry. Preferably, the viscosity of the first negative electrode active slurry is 4000-5000 mPa·s; the viscosity of the second negative electrode active slurry is 3000-4000 mPa·s; and the viscosity of the third negative electrode active slurry is 2500-3500 mPa·s. (4) The solid content of the first negative electrode active slurry, the second negative electrode active slurry and the third negative electrode active slurry is 45%-55%.

6. The preparation method according to claim 4, characterized in that In the step S1, the carbon-coated secondary graphite particles are obtained by granulating and carbon-coating primary graphite particles; The primary graphite particles include primary artificial graphite particles and / or primary natural graphite particles; wherein the primary artificial graphite particles include one or more of needle coke, petroleum coke, pitch coke and mesophase carbon microbeads, and the primary natural graphite particles include flake graphite and / or microcrystalline graphite; The precursors used for the carbon coating include one or more of coal tar pitch, petroleum pitch, coal liquefaction pitch, ethylene tar pitch, natural pitch, anthracite, mesophase carbon microbeads, coconut shell, cotton, trees, glucose, lignin, cellulose, phenolic resin, polyaniline and polyacrylonitrile.

7. The preparation method according to claim 4, characterized in that In step S1, the preparation of the heteroatom-doped hard carbon comprises the following steps: uniformly mixing a hard carbon source and a heteroatom dopant, and then carbonizing the mixture under an inert atmosphere to obtain the heteroatom-doped hard carbon; wherein, The hard carbon source includes one or more of coconut shell, cotton, trees, glucose, lignin, cellulose, phenolic resin, polyaniline and polyacrylonitrile; The heteroatom dopant includes one or more of borane, borax, boron tetrachloride, urea, ammonium chloride, ammonium sulfate, ammonium dihydrogen phosphate, elemental sulfur, thiourea, polyvinylidene fluoride, ammonium hexafluorophosphate, and potassium hexafluorophosphate; The mass ratio of the hard carbon source to the dopant is 10:(1-5); The carbonization temperature is 1200-1800° C., and the carbonization time is 1-5 hours.

8. The preparation method according to claim 4, characterized in that In step S1, the porous carbon nanowire fibers are first crushed and then mixed with a third conductive agent, a third binder, a third thickener, and a third solvent to prepare a third negative electrode active slurry; The preparation of the porous carbon nanofiber comprises the following steps: (1) mixing phenolic resin, polyacrylonitrile, zinc salt and solvent to obtain a spinning solution; (2) subjecting the spinning solution prepared in step (1) to electrospinning to obtain a raw silk fiber material; (3) The raw fiber material prepared in step (2) is carbonized under an inert atmosphere to obtain the porous carbon nanofiber.

9. The preparation method according to claim 8, characterized in that Contain at least one of the following characteristics: (1) In step (1), the mass proportion of zinc salt in the spinning solution is 0.5%-1.5%; (2) In step (1), the zinc salt includes one or more of zinc nitrate, zinc chloride, zinc oxide, and zinc phytate; (3) In step (2), in the electrospinning treatment step: the injection rate is 0.5-1.2 mL / min, the voltage is 16-20 kV, the temperature is 20-25 ° C, and the humidity is 20%-40%; (4) In step (3), the temperature of the carbonization treatment is 1000-1500°C, and the time of the carbonization treatment is 1-5 hours.

10. A lithium ion battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet according to any one of claims 1 to 3 or the negative electrode sheet prepared by the preparation method according to any one of claims 4 to 9.

Citation Information

Patent Citations

  • Negative electrode plate and lithium ion battery

    CN113764617A

  • Lithium ion battery hierarchical composite negative electrode and preparation method and application thereof

    CN113921758A

  • Negative plate as well as preparation method and application thereof

    CN114497451A

  • Lithium battery negative plate, battery cell and lithium battery

    CN116014074A

  • Super fast charging negative pole piece structure

    CN117913208A

Cited By

  • Negative plate and preparation method thereof

    CN121641834A

  • Positive plate and lithium ion battery

    CN121662740A